Relationship of Patient Characteristics and Revisit of Outdoor Patients of Coronary Heart Disease in Hospitals - Desinta Aisyah Nur Dwi Azizah; Alvira Lendriana Scarletta; Arifa Putri Rismanti; Nabilatul Fanny (Proceeding of International Conference on Science, Health, And Technology, 2021)
Based on a survey at the hospital, outpatient visits with coronary heart disease had increased from the previous year, namely 50 patients (2017) and 120 patients (2018). This study aims to determine the relationship between patient characteristics and re-visit of outpatients with coronary heart disease. The type of research used in this research is quantitative research, the sample used is 120 patients. Data were collected by means of a questionnaire and then analyzed by using the Chi-Square test. The results showed that the highest age was 58-67 years (39.9%), the highest gender was male (73.3%), the highest payment method was general patients (63.3%), the highest patient origin was patients came of their own accord (63.3%) and complications of the disease, there were complications that existed in the amount of 72.1%. Chi-Square test results were age (p = 0.037), gender (p = 0.0001), method of payment (p = 0.0001), patient origin (p = 0.0001) and disease complications (p = 0.0001) there is a connection with a repeat visit. The most related logistic regression test results were the method of payment and the origin of the patient with a value of p = 0.0001. It is known that the characteristics of age, sex, method of payment, patient origin and disease complications are associated with repeat visits, while the most related ones are payment methods and patient origins. Suggestions that can be conveyed are to be able to maintain superior services that have been in great demand by patients for treatment.